Functional complementation of a conserved non protein-coding element (CNE) of Autographa californica multiple nucleopolyhedrovirus by heterologous CNE originating from Malacosoma neustria nucleopolyhedrovirus - Kikhno, I.M.; Makarenko, V.E.; Kashuba, V.I. (Вiopolymers and Cell, 2016)
Aim. To assess the functional conservation of a baculovirus CNE. Methods. CNE deletion from the baculovirus genome and its replacement with a heterologous CNE was performed by using the bacmid-based technology. Transfection-infection assays were used to investigate cell-to-cell spread of the recombinant virus. Results. The recombinant Autographa californica multiple nucleopolyhedrovirus genome carrying the Malacosoma neustria nuclepolyhedrovirus CNE in place of the innate CNE was constructed. The recombinant virus was able to transmit the infection in a cell culture. Conclusions . The CNE essential function was foundto be conserved between the representatives of I and II groups of the genus Alphabaculovirus.